PENERAPAN TECHNOLOGY ACCEPTANCE MODEL TERHADAP PENERIMAAN PENGGUNA AKHIR E-LEARNING STMIK STIKOM BALI - Shandyastini, Ni Made; Pradnyani Novianti, Kadek Dwi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
E-learning allows students of STMIK STIKOM Bali to keep learning even though physically absent or unable to attend when the learning process going on in the classroom. The utilization of e-learning can also make the development a high learning flexibility. The perception of the user in this case is a student will be indispensable in order to assist the utilization of e-learning optimally. The goal of this research will examine about admissions in the utilization of e-learning used in STMIK STIKOM Bali. The behavior of students needed to know what the students felt towards e-learning. The research will be focused on reviewing the acceptance of the use of e-learning in accordance with the model of the Technology Acceptance Model (TAM). Analysis of the results obtained showed that the student respondents on this aspect of convenience and expediency of having a positive influence to the attitude when using e-learning, even on the final results of the e-learning has not been well received by the users (students). Whereas, on the usefullnes aspects of the lecturer, respondents have influence nearly all other aspects, so that the final result obtained is lecturer receives well the use of e-learning in the learning process. Further research can be developed by developing indicators for each variable.Â Â Keyword : TAM, e-learning, PLS